Acute kidney injury requiring dialysis after endovascular intervention for acute deep venous thrombosis: A case report and literature review - Najlaa Essa A. H. Al‐Mannai (21841775) (2024)
Key Clinical Message Percutaneous precutaneous mechanical thrombectomy has been used for clot dissolution and removal in selected cases of iliofemoral deep vein thrombosis. Intravascular Hemolysis and hemoglobinuria caused by pharmachomechanical chather directed thrombolysis (PCDT) devices like the Angiojet is associated with an increased risk of acute kidney injury (AKI). Acute tubular necrosis that is severe enough to require hemodialysis can occur. Clinicians should be aware of this potential risk to ensure early recognition and timely referral to the nephrologist, and a clear explanation of the risk of AKI should be given to the patients undergoing this procedure. Lower extremity deep vein thrombosis (DVT) is a frequently encountered medical condition, and one that can lead to death or major disability if not promptly treated. Anticoagulation alone may not always be enough for complete treatment. It has been reported that early thrombus removal can rapidly relieve symptoms and prevent disease progression in some selected cases. Percutaneous pharmacomechanical thrombectomy has been used for clot dissolution and removal in such cases. AngioJet is an increasingly used method of percutaneous mechanical thrombectomy for DVT that can cause intravascular hemolysis and potentially acute kidney injury (AKI). We report here a case of a 39 years old lady who developed severe AKI (illustrated by creatinine level of 664 μmol/L (7.5 mg/dL), bicarb of 13 mmol/L and being anuric), requiring hemodialysis secondary to intravascular hemolysis and hemoglobinuria that occurred immediately after the use of AngioJet pharmacomechanical catheter‐directed technique to treat an extensive iliofemoral DVT. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.9263